Bery Engebretsen letter to Jim Dinsmore regarding summer bird sightings, August 1, 1995 - Engebretsen, Beryet al (1995)
Letter from Bery Engebretsen to Jim Dinsmore dated August 1, 1995. Engebretsen lists birds he sighted during the summer season. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1995. Epson - sheet feed/flatbed